2008
DOI: 10.1016/j.addbeh.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis withdrawal is common among treatment-seeking adolescents with cannabis dependence and major depression, and is associated with rapid relapse to dependence

Abstract: Recently, reports have suggested that cannabis withdrawal occurs commonly in adults with cannabis dependence, though it is unclear whether this extends to those with comorbid depression or to comorbid adolescents. We hypothesized that cannabis withdrawal would be common among our sample of comorbid adolescents and young adults, and that the presence of cannabis withdrawal symptoms would be associated with a self-reported past history of rapid reinstatement of cannabis dependence symptoms (rapid relapse). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 20 publications
6
83
2
Order By: Relevance
“…Of interest was that in contrast to SCB studies reporting poly substance use (Schifano et al 2010;Vandrey et al 2012;Winstock and Barratt 2013;Caviness et al 2015), dependent users in this study smoked only the identified herbal mixtures containing 5f-AKB48 and 5F-PB-22, and used alcohol and cannabis only when attempting to self-detoxify in efforts to alleviate withdrawals. Severity of natural cannabis withdrawal has predictive validity in use of cannabis or other substances to alleviate symptoms (Copersino et al 2006;Chung et al 2008;Cornelius et al 2008). The study highlights the need for the generation of evidence based medical and psychiatric treatment and detoxification protocols for this particularly severe form of synthetic cannabis withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest was that in contrast to SCB studies reporting poly substance use (Schifano et al 2010;Vandrey et al 2012;Winstock and Barratt 2013;Caviness et al 2015), dependent users in this study smoked only the identified herbal mixtures containing 5f-AKB48 and 5F-PB-22, and used alcohol and cannabis only when attempting to self-detoxify in efforts to alleviate withdrawals. Severity of natural cannabis withdrawal has predictive validity in use of cannabis or other substances to alleviate symptoms (Copersino et al 2006;Chung et al 2008;Cornelius et al 2008). The study highlights the need for the generation of evidence based medical and psychiatric treatment and detoxification protocols for this particularly severe form of synthetic cannabis withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Adult users, particularly those with violence problems, report some instances of aggression during intoxication, but these instances are rare, particularly in comparison to experiences of relaxation during intoxication (Arendt et al, 2007). Research should examine self-report of aggressive A C C E P T E D M A N U S C R I P T The most likely way marijuana could pharmacologically contribute to aggression is through the symptoms of cannabis withdrawal, which can occur in adolescents ceasing prolonged, heavy use, particularly among those with a history of conduct disorder or depression (Cornelius et al, 2008;Vandrey et al, 2005). Cannabis withdrawal causes increases in self-rated aggression (31% of adolescents suffering cannabis withdrawal report a moderate or severe increase in aggression) (Vandrey et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Another study of a sample of adolescents and young adults seeking treatment for depression symptoms and cannabis dependence symptoms found that 91% experienced at least two symptoms and 73% experienced at least four symptoms of cannabis withdrawal (Cornelius, Chung, Martin, Wood, & Clark, 2008).…”
Section: Cannabis Withdrawal Syndrome In Adolescentsmentioning
confidence: 99%
“…However, its reliability and validity have since been demonstrated in preclinical, clinical, and epidemiologic studies (Agrawal et al, 2008;Budney & Hughes, 2006;Budney et al, 2004;Copersino et al, 2006;Goldstein & Volkow, 2011;Hasin et al, 2008;Martinez et al, 2007). The clinical significance of cannabis withdrawal is indicated by the use of cannabis or similar substances to relieve withdrawal symptoms, its association with difficulty quitting (Budney et al, 2004;Copersino et al, 2006;Levin et al, 2010), and worse treatment outcomes with greater withdrawal severity Cornelius et al, 2008).…”
Section: Cannabis Withdrawalmentioning
confidence: 99%